Classroom-based interventions across subject areas : research to understand what works in education - Stylianides, Gabriel J.; Childs, Ann (Abingdon, Oxon : Routledge, 2019)
'Written by expert researchers and practitioners, this new book aims to locate the important features of educational research that offer real potential to support improvement of classroom practice in a range of subjects. It considers possible reasons for the scarcity of classroom-based intervention studies, what's involved in adapting interventions for use in different contexts and, crucially, shows how research conducted in real classrooms increases the likelihood of results that are directly applicable to practice and alleviate problems of student learning. It will be essential reading for all those concerned with how educational research can impact upon teaching and learning'--
An introduction to classroom-based interventions across subject areas / Gabriel J. Stylianides and Ann Childs -- Double stimulation for reluctant readers: a literature circle intervention in a secondary school English classroom / Daniel Brocklehurst and Ian Thompson -- What are the possibilities and limitations of small-scale, mediated classroom interventions? : two cases from modern foreign languages / Laura Molway, Trevor Mutton, Robert Woore and Katherine Porter -- Who is doing the questioning : a classroom intervention in secondary science classrooms to promote student questioning / Alexandra Haydon and Ann Childs -- Developing science explanations in the classroom: the role of the written narrative / Richard Taylor and Judith Hillier -- Developing talk in mathematics classrooms / Jenni Ingram, Nick Andrews, Jo Rudd and Andrea Pitt -- The role of practitioner research and publication in developing a cumulative and critical tradition of research in classroom-based interventions in history education / Katharine Burn, Jaya Carrier and Anna Fielding -- Mapping-out the inferential relations of the subject content of geography lessons: a planning intervention for pre-service teachers to inform teaching and learning / Roger Firth and Ali Strutt -- The problems and possibilities of conducting small-scale classroom-based randomised control trials in contributing to evidence-based practice: one school's experience / Elizabeth Samuel, Christina Watson and Ann Childs -- Commentary classroom-based interventions in different subject areas: sharing meaning across researchers and practitioners / Merrilyn Goos -- Commentary interventions in education : origins, theoretical perspectives and challenges / Shirley Simon.
Includes bibliographical references.
Keywords: Teacher effectiveness; Effective teaching; Observation (Educational method).; Education -- Research -- Methodology